PENGARUH PAD, DAU, DAN SILPA TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI MODERASI - Yohanes Septo Wahyu Kristiyan, 12.05.52.0201; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
Regional autonomy is directed to improve overall welfare of the community through service improvement, empowerment and community participation. Regional autonomy is intended to sharpen the essence of financial management in local government administration system concerning the elaboration of the rights and obligations in the management of public finances. This study aims to determine the effect of the pad, dau, and Silpa towards capital expenditure with economic growth as moderating. The population in this study is the public sector finances from 2013 to 2015. The sample in this study were taken by purposive sampling method. Data were analyzed using skewness-kurtosis normality test, classic assumption test, koofisiendeterminasi test, F test and test hypotheses. The test results In the variable PAD, DAU and PE statistically positive effect SILPA At variables are statistically not significant effect on capital spending. The results of the economic growth variable is not found moderating effect of PAD and DAU to capital expenditures.Keywords: PAD, DAU, Silpa, Economic Growth, Capital Expenditure